Reduplication in Malay. - Nur Hairiana Alikamal. (2012)
Although Austronesian languages are recognized for utilizing reduplication, no studies have been done on reduplication in Classical Malay. This study examines the morphosyntactic and semantic properties of reduplicated nouns and verbs in Classical Malay literature from the 1500s. It is also the first study of its kind to offer a diachronic perspective in the use of reduplication in Classical Malay and Modern Malay. Authentic Classical Malay texts – HPL, HSR and HIZ – from the Malay Concordance Project was used, and reduplicated words found in these texts were rated using a 5-point rating system. This rating system was based on my own language judgment and instinct, and assessed according to the language environment in Singapore. The findings show that reduplication in nouns mark only diversity in Classical Malay, but this semantic value has expanded to mark both diversity as well as plurality in Modern Malay. There was also a lesser use of RED[N]-AN due to the analogical pressure of full reduplication in nouns. The shift in function for RED[N]-AN in Modern Malay is also significant, and now marks adverbial and adjectival meanings. However, only semantic values of nouns are stifled; the semantic values of verbs remain mostly the same in Modern Malay.